STRATEGY OF COMMUNITY SOCIAL CARE MANAGEMENT (PPKM) IN IMPROVING COMMUNITY WELFARE IN SENGON SARI VILLAGE, AEK KUASAN DISTRICT, ASAHAN REGENCY - Pendi Santoso; Jhon Simon; Muzayanah Br Depari (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Improving rural community welfare does not depend on government policy alone. It requires the active role of communities through community-based social initiatives. One such initiative is the PPKM AlIkhlas (Pengurus Peduli Kesosialan Masyarakat) programme in Sengon Sari Village, Aek Kuasan Subdistrict, Asahan Regency. This programme reflects social solidarity in supporting villagers facing social and economic difficulties. The study aims to analyse the strategies of PPKM Al-Ikhlas in improving community welfare, to identify the supporting and inhibiting factors of programme implementation, and to describe the contribution of the programme to community welfare in the village. A qualitative descriptive method was used. Data were collected through interviews, observation, and documentation. Informants comprised PPKM Al-Ikhlas committee members, village officials, community leaders, and beneficiary residents. Data were analysed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that the strategies adopted by PPKM Al-Ikhlas rely on participatory approaches, community deliberation, and direct service to those in need. Supporting factors include strong values of mutual cooperation, community-level social concern, and trust in the committee. Inhibiting factors include limited financial resources, simple administrative management, and uneven community participation. The programme has contributed positively to community welfare, both through the fulfilment of basic needs and the strengthening of social solidarity. PPKM Al-Ikhlas thus functions as a community-based social initiative that complements the role of village government in advancing rural welfare. Keywords: Strategy; PPKM; Community Welfare; Social Initiative; Sengon Sari Village